A construção da ideia de masculinidade como falha cultural na sociedade estadunidense em watchmen - Silva, Ícaro Andriêr Soares da (Universidade Federal Rural do Semi-Árido, 2019)
This work aims to investigate the construction of the idea of masculinity as a cultural failure in American society by reading Watchmen and will be developed trying to answer the following question: are the demonstrations of masculinity in Watchmen sign of full virility or do they hide traces of the impotence generated by the non-repetition of the war hero, who took over the American culture in the second half of the twentieth century? To answer this question, we will contextualize, from a critical bibliographical survey, the study on masculinity in the twentieth century by Susan Faludi (2006), as well as the theoretical and methodological aspects of studies on the genre comics (McCLOUD, 1994; EISNER, 2000 ), and finally, the masculinity performances of the characters Comedian, Dr. Manhattan and Rorschach will be analyzed, considering the contradictions and failures of the ideal of virility attached to them and the society to which they belong. The relevance of the research lies in the fact that it helps to demystify the idea that studying masculinity is masculinist, that is, we believe that studies about men are not opposed to studies on women, since they seek to ascertain the effects and pressures that men also suffer to suit the ideal of man imposed by society. We conclude that the signs of virility presented by the characters in the plot hide traces of the impotence generated by the non-repetition of the war hero who settled in American culture in the second half of the twentieth century.
Monografia
Keywords: Quadrinhos; Masculinidade; Impotência; Virilidade; Pós-guerra; LINGUISTICA, LETRAS E ARTES::LETRAS::LETRAS INGLESA